Identifying Symbolic Violence in the Comic Version of “Cinderella” - Linda, Juliana (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This study aims to identify and analyze instances of symbolic violence, a concept introduced by Pierre Bourdieu, in the comic adaptation of the short story